2010
DOI: 10.1175/2009jhm1006.1
|View full text |Cite
|
Sign up to set email alerts
|

A 1–10-Day Ensemble Forecasting Scheme for the Major River Basins of Bangladesh: Forecasting Severe Floods of 2003–07*

Abstract: This paper describes a fully automated scheme that has provided calibrated 1-10-day ensemble river discharge forecasts and predictions of severe flooding of the Brahmaputra and Ganges Rivers as they flow into Bangladesh; it has been operational since 2003. The Bangladesh forecasting problem poses unique challenges because of the frequent life-threatening flooding of the country and because of the absence of upstream flow data from India means that the Ganges and Brahmaputra basins must be treated as if they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 28 publications
(18 reference statements)
0
93
0
2
Order By: Relevance
“…Several flood forecasting systems are based on observed river level, while future values are extrapolated through river routing models or by coupling observed rainfall fields into hydrological models. The extension of the forecast horizon beyond the response time of a river basin is enabled by the use of numerical weather predictions (NWPs) as input to hydrological-hydraulic models (e.g., He et al, 2010;Hopson and Webster, 2010;Paiva et al, 2012;Thiemig et al, 2010). Recent review articles by Cloke and Pappenberger (2009) and by Alfieri et al (2012a) showed the strong potential of using ensemble NWPs to further extend the forecasting horizon in early warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several flood forecasting systems are based on observed river level, while future values are extrapolated through river routing models or by coupling observed rainfall fields into hydrological models. The extension of the forecast horizon beyond the response time of a river basin is enabled by the use of numerical weather predictions (NWPs) as input to hydrological-hydraulic models (e.g., He et al, 2010;Hopson and Webster, 2010;Paiva et al, 2012;Thiemig et al, 2010). Recent review articles by Cloke and Pappenberger (2009) and by Alfieri et al (2012a) showed the strong potential of using ensemble NWPs to further extend the forecasting horizon in early warning systems.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is critical in the transboundary or international river basins where it is almost impossible to obtain reliable precipitation data from the upstream regions in near realtime due to hydropolitical issues [Hopson and Webster, 2010;Hossain et al, 2007;Hossain and Katiyar, 2006]. A report by UN-Water [2008] shows that 40% of the global population resides in the 263 transboundary or International River basins.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties from the structure of the hydrological model, i.e., in the mathematical representation of the hydrological processes involved in the rainfall-runoff transformation, were however not considered. An operational forecasting system that takes into account model uncertainty is presented by Hopson and Webster (2010) for the Brahmaputra and Ganges Rivers. It is based on the ECMWF 51-member ensemble prediction system and two hydrological models (semi distributed and lumped).…”
Section: Introductionmentioning
confidence: 99%